Preparation method of Sm-doped LuAG laser crystal
Through horizontal directional crystallization method and in-situ annealing technology, the problems of high cost and poor quality of Sm-doped LuAG laser crystals are solved, and efficient and low-cost high-quality crystal preparation is achieved.
Patent Information
- Application Number
- CN202510366193.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-06-17
AI Technical Summary
In the prior art, the cost of preparing Sm-doped LuAG laser crystals is relatively high, and the quality of the obtained crystals is poor.
The horizontal directional crystallization method is adopted to achieve uniform doping of Sm3+ by controlling the length and growth rate of the melting zone, and in-situ annealing technology is used to reduce the stress in the crystal, improving the yield and production stability.
It reduces the preparation cost, improves the crystal quality, realizes the uniform doping of Sm3+ in the LuAG matrix, and enhances the energy storage capacity and laser conversion efficiency of the crystal.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of crystal preparation, and particularly relates to a method for preparing Sm-doped LuAG laser crystal. Background Art
[0002] Orange-yellow lasers (wavelength range 580 - 620 nm) have broad application prospects in fields such as medicine, astronomy, remote sensing, and visual display. In recent years, with the significant progress of GaN and InGaN semiconductor laser diode (LD) technology in the blue light region, researchers have begun to focus on new materials that can achieve efficient red-orange light output under direct pumping by a 405 nm wavelength laser diode.
[0003] Among many candidate materials, laser crystals doped with trivalent samarium ions (Sm³⁺) have attracted much attention due to their high absorption coefficient, long fluorescence lifetime, and excellent luminescence properties at a wavelength of 405 nm. Sm³⁺ is based on 4 G 5 / 2 → 6 H 7 / 2 energy level transitions and can emit orange-yellow light of about 600 nm, which is exactly within the target range. In addition, the large energy gap between the excited state and the lower energy level of Sm³⁺ reduces the multi-phonon relaxation effect, thus helping to lower the laser threshold. Compared with Pr³⁺, the 5d energy level of Sm³⁺ requires a higher value and is more suitable for materials in a strong crystal field environment, which makes Sm³⁺-doped visible light gain medium materials a research hotspot.
[0004] Currently, researchers have explored various matrix materials doped with Sm³⁺, such as double borate crystals, fluoride crystals, and gallate crystals. However, these materials still have many deficiencies in practical applications, such as large phonon energy, poor thermo-mechanical properties, or high preparation difficulty. Therefore, developing a matrix material with excellent physical and chemical properties has become the focus of current research.
[0005] Lutetium aluminum garnet (LuAG) has been widely used as a matrix material for laser gain media due to its high thermal conductivity, excellent optical, thermodynamic, mechanical properties, and chemical stability. By doping Sm³⁺ ions into LuAG crystals, LD-pumped orange-yellow laser output can be achieved. In addition, the luminescence efficiency of Sm³⁺ in the LuAG matrix can be further improved by optimizing the doping concentration and crystal growth process, thereby enhancing the energy storage capacity and laser conversion efficiency of the crystal.
[0006] The LuAG matrix has a cubic crystal structure and a melting point as high as 2010 °C, making it suitable for preparation by the melt method. However, although the traditional Czochralski method is widely used, its high cost and the problem of easy defect generation have prompted researchers to explore more efficient and low-cost preparation methods. This can not only meet the market demand for new high-performance laser materials but also promote the further development of red-orange light laser technology.
[0007] In summary, developing Sm³⁺-doped LuAG crystals and optimizing their preparation processes are the keys to achieving efficient orange-yellow laser output. This research direction not only has important scientific significance but also broad application prospects. Summary of the Invention
[0008] Aiming at the above deficiencies of the existing technology, the purpose of the present invention is to provide a preparation method for Sm-doped LuAG laser crystals, which solves the problems of high cost and poor crystal quality in the preparation of Sm-doped LuAG laser crystals by the existing technology.
[0009] To solve the above technical problems, the technical solution adopted by the present invention is as follows: A preparation method for Sm-doped LuAG laser crystals includes the following steps: (1) Spread the Sm-doped LuAG pre-crystallized material flat in a boat-shaped crucible. Then, insert the seed crystal into the seed crystal groove at one end of the boat-shaped crucible near the shoulder angle. After that, place the boat-shaped crucible containing the pre-crystallized material and the seed crystal into the working furnace, and make the equal-width area of the boat-shaped crucible located in the heating area of the working furnace, and close the furnace chamber; (2) Turn on the water-cooling cycle and evacuate the working furnace. When the vacuum degree is less than 9.9×10 -3 Pa, turn on the heating power supply of the working furnace to heat the pre-crystallized material in the boat-shaped crucible in the heating area. By controlling the heating power, make the pre-crystallized material in the heating area melt to form a narrow melt zone, the length of the melt zone is 15 - 25 mm, and keep it warm for 20 - 60 min to ensure the stability of the melt state; After the melt is stabilized, horizontally move the boat-shaped crucible to align the heating area with the end of the boat-shaped crucible containing the seed crystal for heating, while ensuring that the seed crystal is located at the edge of the heating area, and keep the temperature for 20 - 60 min. When the pre-crystallized material in contact with the seed crystal just melts and the seed crystal neither melts nor grows, move the boat-shaped crucible slowly towards the end of the boat-shaped crucible containing the seed crystal at a growth rate of 1 - 2 mm / h, successively passing through seeding and shoulder growth. After the shoulder growth ends, keep the heating power unchanged, and move the boat-shaped crucible slowly towards the end of the boat-shaped crucible containing the seed crystal at a growth rate of 2 - 3 mm / h until all the pre-crystallized material is completely melted and crystallization is completed. After cooling and annealing, the Sm-doped LuAG crystal is obtained; during the moving process, the melt in the part of the boat-shaped crucible gradually away from the heating area generates supercooling degree, which serves as the crystallization driving force to promote the generation of single crystals.
[0010] Furthermore, the procedure of the cooling and annealing in step (3) is as follows: first, reduce the furnace temperature to 1100 - 1400 °C at a cooling rate of 15 - 30 °C / h, and keep the temperature at this temperature for 40 - 60 h for in-situ annealing to reduce the internal thermal stress of the crystal. Subsequently, cool it to room temperature at a cooling rate of 30 - 60 °C / h, open the furnace, and take out the crystal. During the cooling and annealing process, although a too fast cooling rate or too short holding time can reduce the crystal growth cycle, a too fast cooling rate and too short holding time will weaken the elimination degree of stress during annealing and increase the cracking risk. Therefore, the present invention adopts a segmented cooling method for annealing. First, cool at a smaller rate to gradually stabilize the internal structure of the crystal and keep the temperature for 40 - 60 h to eliminate the internal stress of the crystal, and then cool to room temperature at a faster speed, which improves the crystal preparation efficiency. Adopting this in-situ annealing technology significantly improves the yield of the crystal and enhances the stability and reliability of the overall production.
[0011] Furthermore, the preparation method of the Sm-doped LuAG pre-crystallized material in step (1) is as follows: weigh the powder raw materials Sm2O3, Lu2O3, and Al2O3 according to the chemical stoichiometric ratio of the chemical formula Lu 3(1-x) Sm 3x Al5O 12 Then, after mixing the raw materials evenly, melt and cool to obtain a solid solution, and then break the solid solution into small pieces as the pre-crystallized material; where x is the doping concentration of Sm 3+ , and the value of x is 0.1 - 10 at%.
[0012] Furthermore, the seed crystal in step (1) adopts the <111>, <100>, or <110> direction.
[0013] Further, the shoulder angle during the shoulder-forming stage is 80 - 120°. The shoulder angle should not be too large or too small. When the shoulder angle is too small, the part of the crystal before shoulder formation cannot be reasonably utilized, resulting in a low crystal utilization rate. If it is too large, it will cause difficulties in shoulder closing. When the shoulder angle is 90°, the entire ingot can be most reasonably utilized, well solving the problem of ingot utilization rate, and at the same time, shoulder closing is relatively easy. Therefore, the preferred shoulder angle is 90°.
[0014] Further, the boat-shaped crucible is a boat-shaped molybdenum crucible. The molybdenum crucible used in the present invention has a melting point of 2630 °C, which is easy to grow crystals with high melting points. During the growth process, the crucible has high stability, is not prone to leakage, and has low cost, increasing production efficiency.
[0015] The present invention prepares Sm-doped LuAG crystals by the horizontal directional crystallization method. During the single crystal growth process, by controlling the length of the molten zone to be 15 - 25 mm, the growth rates of seed crystal and shoulder formation to be 1 - 2 mm / h, and the growth rate of the equal-width growth stage to be 2 - 3 mm / h, uniform doping of Sm 3+ is achieved. The reason for controlling the length of the molten zone within 15 - 25 mm is to obtain a narrow molten zone. Because for the zone melting method of a solute non-conservative system, the shorter the length of the molten zone, the more uniform the distribution of the grown crystal, so as to reduce the doping ion concentration caused by the segregation effect 3+ from gradually increasing with the increase of crystal growth time, thereby achieving the purpose of controllable composition. However, the length of the molten zone should not be too short either, because if the length of the molten zone is too short, it is easy to generate supercooled melt or locally supercooled melt, which is not conducive to the stability of the growth interface. An unstable interface is prone to generate dendrites or cellular structures, which is not conducive to obtaining high-quality crystals. At the same time, during the crystal growth process, a certain temperature is also required to maintain the fluidity of the melt. Too low temperature (or too small molten zone) will lead to very poor fluidity of the melt, thus affecting crystal growth.
[0016] The inventors of the present invention found through research that the segregation coefficient is closely related to the radii of the doping ions and the host ions (the host ion in YAP crystal is Y 3+ , the host ion in CaDyAlO4 crystal is Dy 3+ , and the host ion in LuAG crystal is Lu 3+ ). Generally speaking, the smaller the difference between the radius of the doping ion and the radius of the host ion (the ion to be replaced), the closer the segregation coefficient is to 1. The radius of Y 3+ is 1.281 Å, the radius of Lu 3+ is 0.861 Å, the radius of Sm 3+ is 0.95 Å, and the radius of Dy 3+ is 0.912 Å. It can be seen that the radius difference between Sm 3+ and Lu 3+ is within the range of Sm3+ and Y 3+ radius difference, and Sm 3+ and Dy 3+ radius difference. Therefore, the segregation coefficient of Sm 3+ in LuAG can be determined according to the segregation coefficients of Sm 3+ in YAP and CaDyAlO4. The segregation coefficient of Sm 3+ in LuAG lies between the segregation coefficients of Sm 3+ in YAP (segregation coefficient is 0.643) and CaDyAlO4 (segregation coefficient is 0.985).
[0017] It can be seen from this that the segregation coefficient of Sm 3+ ions is close to 1. During the growth process, it is not easy to generate defects such as white filaments and clouds due to constitutional supercooling. Therefore, it can be grown at a smaller temperature gradient (smaller melt zone length) and a larger growth rate. However, in order to ensure the smooth progress of the seeding process and increase the stability of the interface to avoid the generation of defects, the seeding growth is carried out at a slower speed at the beginning, and the speed is increased during the isothermal growth stage, so as to ensure the high-quality growth of the crystal. The present invention realizes the uniform doping of Sm 3+ in the LuAG matrix by reasonably controlling the melt zone length and the growth rate, and obtains a high-quality Sm-doped LuAG crystal with uniform doping of Sm 3+ uniformly doped.
[0018] 1. The preparation method of the Sm-doped LuAG laser crystal of the present invention adopts a zone melting method in which a single crystal, a melt, and a pre-crystallized polycrystalline raw material coexist during the single crystal growth process, and the melt zone is controlled within a specific size range to form a narrow melt zone for the pre-crystallized polycrystalline raw material, so as to obtain a solute non-conservative system, thereby controlling the composition (distribution of doped ions) to realize the uniform doping of Sm 3+ in the LuAG matrix, and by reasonably controlling the growth rate, a high-quality Sm-doped LuAG crystal with uniform doping of Sm 3+ is obtained. The crystal prepared by this method has high quality, no defects such as core and side core, and solves the problem that it is difficult to prepare a high-quality Sm-doped LuAG crystal with controllable and uniform composition by the existing crystal growth methods. And the method is simple and easy to implement, and the preparation efficiency is relatively high.
[0019] 2. The boat-shaped molybdenum crucible used in the present invention has a relatively low cost, a large free upper surface, accounting for 35%-40% of the total melt contact area. The grown crystal has a relatively low dislocation density, and the height of the boat-shaped crucible is much smaller than its length, which creates favorable conditions for the evaporation of impurity components in the melt, facilitating the effective reduction of crystal scattering, improving the transparency and optical properties of the crystal. Moreover, there is no rotation operation in the present invention, combined with a relatively low melt height, which makes there be almost no convection movement in the melt, increasing the stability of the growth front, and the grown crystal has no core and side core, making it easy to obtain high-quality crystals. At the same time, the machining allowance is reduced, the difficulty of later processing is lowered, and the production efficiency is significantly improved. In addition, during crystal preparation, in-situ annealing is adopted to reduce the internal stress in the crystal and reduce the possibility of crystal cracking.
[0020] 3. Before the seeding growth in the present invention, the equal-width area of the boat-shaped crucible is first heated to melt the polycrystalline material to obtain a narrow melt zone, and then the end close to the seed crystal is heated at the same power, and then the seeding growth is carried out slowly. The reason for doing this is that the shape of the equal-width area is a cuboid, which is convenient for observing the temperature situation and judging whether the solid-liquid interface is stable. The front end of the crucible where the seed crystal is located is triangular, and the solid-liquid interface is very short, making it difficult to judge whether the solid-liquid interface is stable and more difficult to control the power, which easily increases the risk of excessive melting of the seed crystal. The above method avoids the risk of excessive melting of the seed crystal, has a lower operation difficulty and a smaller risk, and is convenient for popularization and application.
[0021] 4. The present invention can grow high-quality Sm-doped LuAG plate crystals with dimensions greater than or equal to 160mm×100mm×30mm, having a low defect density, a high transmittance, and excellent optical properties, meeting the requirements of high-end lasers and optical systems. During actual production, the crucible size can also be adjusted according to requirements to change the crystal size. Detailed implementation mode
[0022] The following combines specific embodiments to further describe the detailed implementation mode of the present invention in detail. Embodiment
[0023] This embodiment provides a method for preparing an Sm-doped LuAG laser crystal, including the following steps: (1) Furnace loading: Select Sm2O3, Lu2O3, and Al2O3 powders with a purity of 5N, and according to the chemical formula Lu 3(1-x) Sm 3x Al5O 12Ingredients are proportioned according to the stoichiometric ratio, where x = 0.2 at%, and the raw materials of each component are weighed to make the total mass of the raw materials reach 2 kg. Subsequently, the raw materials are mixed evenly and melted and cooled to obtain a solid solution. Then, the solid solution is broken into small pieces as the pre-crystallization material. Subsequently, the pre-crystallization material is laid flat in a boat-shaped molybdenum crucible after alcohol washing, and a pure LuAG seed crystal is inserted into the seed crystal groove at one end of the boat-shaped molybdenum crucible near the shoulder angle, and the seed crystal direction is <100>. Then, the boat-shaped molybdenum crucible containing the pre-crystallization material and the seed crystal is placed in a single crystal furnace, and the equal-width area of the boat-shaped molybdenum crucible is located in the heating area of the single crystal furnace. Subsequently, the furnace chamber is closed; (2) Melting the pre-crystallization material: Turn on the water-cooling cycle and start the vacuum pump to extract vacuum to avoid the influence of impurity gases on crystal preparation. When the vacuum degree reaches 8×10 -4 Pa, turn on the heating power supply of the single crystal furnace and perform resistance heating to raise the temperature of the heating area. When the temperature of the heating area reaches 2080 °C, liquid flow lines appear inside the melt. Adjust the heating power at a rate of 0.2 kW / h to form an orderly convection solid-liquid transformation phenomenon on the liquid surface, and control the length of the molten zone to be 22 mm. Keep it at this temperature for 30 min to ensure the stability of the melt state; (3) Seed crystal introduction, shoulder release, and equal-width growth: After the melt is stable, move the boat-shaped molybdenum crucible so that the pre-crystallization material near the seed crystal end is located in the heating area, and the seed crystal is just at the edge of the heating area. Keep the temperature stable for 30 min to ensure the stable state of the interface between the seed crystal and the melt. When the seed crystal contacts the melt and neither melts nor grows, turn on the automatic crucible movement program and move the boat-shaped molybdenum crucible towards the end with the seed crystal at a growth rate of 2 mm / h to perform the seed crystal introduction and shoulder release growth processes in sequence. After the shoulder release is completed, keep the heating power unchanged and move the boat-shaped molybdenum crucible towards the end with the seed crystal at a growth rate of 2.5 mm / h to perform equal-width growth until the crystallization process ends; During the movement, the melt in the part of the boat-shaped molybdenum crucible that gradually moves away from the heating area generates supercooling, which serves as the crystallization driving force to promote the generation of single crystals, and the shoulder angle is 90°.
[0024] (4) Cooling and annealing: After crystallization is completed, enter the cooling and annealing stage. First, cool down at a cooling rate of 30 °C / h to the annealing temperature of 1200 °C and keep it for 40 h; Subsequently, cool down to room temperature at a rate of 60 °C / h, and finally open the furnace and take out the crystal.
[0025] After testing, the quality of the Sm-doped LuAG crystal grown by this process is good, and the size is 160 mm × 100 mm × 30 mm. Example
[0026] This example provides a method for preparing a Sm-doped LuAG laser crystal, including the following steps: (1)Loading the furnace: Select Sm2O3, Lu2O3 and Al2O3 powders with 5N purity, and mix them according to the stoichiometric ratio of the chemical formula Lu 3(1-x) Sm 3x Al5O 12 , where x = 0.5 at%. Weigh the raw materials of each component to make the total mass of the raw materials reach 2.5 kg. Then mix the raw materials evenly, melt and cool them to obtain a solid solution. Then break the solid solution into small pieces as the pre-crystallization material. Subsequently, spread the pre-crystallization material flat in a boat-shaped molybdenum crucible after alcohol washing, and insert a pure LuAG seed crystal into the seed crystal groove at one end of the boat-shaped molybdenum crucible near the shoulder angle. The direction of the seed crystal is <111>. Then place the boat-shaped molybdenum crucible containing the pre-crystallization material and the seed crystal into the single crystal furnace, and make the equal-width area of the boat-shaped molybdenum crucible located in the heating area of the single crystal furnace. Then close the furnace chamber; (2)Melting the pre-crystallization material: Turn on the water-cooling circulation and start the vacuum pump to extract vacuum. When the vacuum degree reaches 6.6×10 -4 Pa, turn on the heating power supply of the single crystal furnace and heat the heating area by resistance heating. When the temperature of the heating area reaches 2060 °C, liquid flow lines appear inside the melt. Adjust the heating power at a rate of 0.1 kW / h to form an orderly convection solid-liquid transformation phenomenon on the liquid surface, and control the length of the melting zone to be 23 mm. Keep it at this temperature for 40 min to ensure the stability of the melt state; (3)Seeding, shoulder releasing, and equal-width growth: After the melt is stable, move the boat-shaped molybdenum crucible so that the pre-crystallization material near the seed crystal end is located in the heating area, and the seed crystal is just at the edge of the heating area. Keep the temperature stable for 40 min to ensure that the interface between the seed crystal and the melt reaches a stable state. When the seed crystal contacts the melt and neither melts nor grows, turn on the automatic crucible movement program, and move the boat-shaped molybdenum crucible towards the end with the seed crystal at a growth rate of 1.5 mm / h to perform the seeding and shoulder releasing growth processes in sequence. After the shoulder releasing is completed, keep the heating power unchanged, and move the boat-shaped molybdenum crucible towards the end with the seed crystal at a growth rate of 2 mm / h to perform equal-width growth until the crystallization process ends. During the movement, the melt in the part of the boat-shaped molybdenum crucible that gradually moves away from the heating area generates supercooling, which serves as the crystallization driving force to promote the generation of single crystals. The shoulder angle is 100º.
[0027] (4)Cooling and annealing: After crystallization is completed, enter the cooling and annealing stage. First, cool it at a cooling rate of 20 °C / h to the annealing temperature of 1300 °C to gradually stabilize the internal structure of the crystal and keep it for 48 h to eliminate the internal stress of the crystal. Then cool it to room temperature at a rate of 40 °C / h. Finally, open the furnace and take out the crystal.
[0028] After testing, the quality of the Sm-doped LuAG crystal grown by this process is good, and the size reaches 140 mm×85 mm×30 mm, meeting the design requirements.
[0029] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit them. Those of ordinary skill in the art should understand that any modifications or equivalent replacements made to the technical solutions of the present invention without departing from the spirit and scope of the present technical solutions shall be covered by the scope of the claims of the present invention.
Claims
1. A method for preparing a Sm-doped LuAG laser crystal, characterized in that: The following steps are involved: (1) Spread the Sm-doped LuAG pre-crystallized material flat in a boat-shaped crucible, then insert the seed crystal into the seed crystal groove at one end of the boat-shaped crucible near the shoulder corner, put the boat-shaped crucible containing the pre-crystallized material and the seed crystal into a working furnace, and make the equal-width area of the boat-shaped crucible located in the heating area of the working furnace, and close the furnace; (2) Turn on the water cooling cycle and evacuate the working furnace. When the vacuum degree is less than 9.9×10 -3 Pa, turn on the heating power of the working furnace to heat the pre-crystallized material in the boat-shaped crucible in the heating area, and control the heating power to melt the pre-crystallized material in the heating area to form a narrow melting zone with a length of 15-25 mm. Keep the temperature for 20-60 minutes to ensure that the melt state is stable; (3) After the melt is stable, the crucible boat is moved horizontally so that the heating area is aligned with the end of the crucible boat containing the seed crystal for heating, while ensuring that the seed crystal is located at the edge of the heating area. The temperature is kept for 20-60 minutes. When the pre-crystallization material in contact with the seed crystal is just melted and the seed crystal is neither melted nor grown, the crucible boat is slowly moved toward the end of the crucible boat containing the seed crystal at a growth rate of 1-2 mm / h, and the seed crystal is sequentially grown through seeding and shoulder release. After the shoulder release is completed, the heating power is kept unchanged, and the crucible boat is slowly moved toward the end of the crucible boat containing the seed crystal at a growth rate of 2-3 mm / h until all the pre-crystallization materials are completely melted and crystallized. After cooling and annealing, Sm-doped LuAG crystals are obtained. During the movement, the melt in the crucible boat that is gradually away from the heating area produces supercooling, which serves as a driving force for crystallization and promotes the production of single crystals.
2. The method for preparing the Sm-doped LuAG laser crystal according to claim 1, characterized in that: The procedure of the cooling annealing in step (3) is as follows: first, the furnace temperature is lowered to 1100-1400°C at a cooling rate of 15-30°C / h, and kept at this temperature for 40-60h for in-situ annealing to reduce the internal thermal stress of the crystal, and then cooled to room temperature at a cooling rate of 30-60°C / h, the furnace is opened, and the crystal is taken out.
3. The method for preparing the Sm-doped LuAG laser crystal according to claim 1, characterized in that: The preparation method of the Sm-doped LuAG pre-crystallized material in step (1) is as follows: 3(1-x) Sm 3x Al5O 12 The powder raw materials Sm2O3, Lu2O3 and Al2O3 are weighed in a stoichiometric ratio, and then the raw materials are mixed evenly, melted and cooled to obtain a solid solution, and then the solid solution is broken into small pieces as a pre-crystallization material; wherein x is Sm 3+ The doping concentration of x is 0.1~10 at%.
4. The method for preparing the Sm-doped LuAG laser crystal according to claim 1, characterized in that: The seed crystal in step (1) is <111> , <100> or <110> direction.
5. The method for preparing the Sm-doped LuAG laser crystal according to claim 1, characterized in that: The shoulder release angle during the shoulder release phase is 80~120º.
6. The method for preparing the Sm-doped LuAG laser crystal according to claim 1, characterized in that: The boat-shaped crucible is a boat-shaped molybdenum crucible.